The Role of Traumatic Event History in Non-medical Use of Prescription Drugs among a Nationally Representative Sample of U.S. Adolescents - McCauley, Jenna L. (2009)
BACKGROUND: Building on previous research with adolescents that examined demographic variables and other forms of substance abuse in relation to Non-medical use of prescription drugs (NMUPD), the current study examined potentially traumatic events, depression, posttraumatic stress disorder (PTSD), other substance use, and delinquent behavior as potential correlates of lifetime non-medical use of prescription drugs. METHOD: Nationally representative sample of 3,614 non-institutionalized, civilian, English speaking adolescents (aged 12-17 years) residing in households with a telephone. Demographic characteristics, traumatic event history, mental health, and substance abuse variables were assessed. NMUPD was assessed by asking if participants had ever used a prescription drug in a non-medical manner. Multivariable logistic regressions were conducted for each theoretically derived predictor set. Significant predictors from each set were then entered into a final multivariable logistic regression to determine significant predictors of lifetime NMUPD. RESULTS: NMUPD was endorsed by 6.7% of the sample (n=242). Final multivariable model showed that lifetime history of delinquent behavior, other forms of substance use/abuse, history of witnessed violence, and lifetime history of PTSD were significantly associated with increased likelihood of NMUPD. CONCLUSIONS: Risk reduction efforts targeting NMUPD among adolescents who have witnessed significant violence, endorsed abuse of other substances and delinquent behavior, and/or endorsed PTSD are warranted. Interventions for adolescents with history of violence exposure or PTSD, or those adjudicated for delinquent behavior should include treatment or prevention modules that specifically address NMUPD.